Transitioning to Breast Cancer Survivorship: Perspectives of Patients, Cancer Specialists, and Primary Care Providers - Kantsiper, Melinda (Springer-Verlag, 2009)
BACKGROUND: Limited research exists regarding views of patients, oncology specialists, and primary care providers (PCPs) concerning breast cancer survivorship care. OBJECTIVE: To qualitatively explore the needs and priorities of breast cancer survivors, oncology specialists, and PCPs. METHODS: Focus groups were conducted of survivors (21 in 5 groups), PCPs (15 in 2 groups), and oncology specialists (16 in 2 groups). One survivor group consisted of four African-Americans. Discussions used a semi-structured guide, were transcribed verbatim, and were analyzed qualitatively. Groups explored transitions to follow-up, communication, patient needs, and provider roles. RESULTS: Survivors form intense relationships with specialists for reassurance and expertise. Many believed PCPs lacked necessary oncology expertise. Survivors reported psychosocial and communication issues. African-Americans cited concerns about access to care and clinical trials, as well as taboos to discussing cancer. Specialists reported that they struggle with discharging survivors due to protective relationships. PCPs were concerned about time and training to provide survivorship care and communication problems with oncologists. Written survivorship care plans were regarded by all groups as possibly helpful, but insufficient to ease the transition. CONCLUSIONS: Breast cancer patients may experience difficulties transitioning to survivorship, including ongoing psychosocial issues. African-American patients may face additional and unique barriers to successful survivorship. Oncology specialists may have concerns about discharging cherished patients. These findings suggest a psychological component that may influence the use of written survivorship care plans. PCPs may need additional training and greater access to specialists in order to care for survivors.